The Libyan position on the Iraqi occupation of Kuwait in 1990-1991 AD - Sabeeh, Ass. Prof. Dr. Ali Jouda; Abdel-Razzaq, Ass. Lect. Zainab Shaker (Thi Qar Arts Journal, 2022)
The Iraqi military occupation of Kuwait on August 2, 1990 AD, constituted a regional and international crisis that made the Arab and Western countries deal with it with great interest, given its direct impact on the security of the Arab Gulf region, to which Western interests are linked. From here came the positions of most countries of the world towards this important event, including The position of the Libyan Jamahiriya stemming from its foreign policy, its Arab and international relations, and its methods of dealing with Arab and international crises, especially the Iraqi-Kuwaiti crisis.